2015
DOI: 10.1111/ene.12754
|View full text |Cite
|
Sign up to set email alerts
|

Biological follow‐up in amyotrophic lateral sclerosis: decrease in creatinine levels and increase in ferritin levels predict poor prognosis

Abstract: Changes to ferritin and creatinine levels with time are associated with ALS progression. This is the first study describing the changes to these biological variables during ALS progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Serum creatinine levels have been reported to change significantly during the progression of other motor neuron diseases. 23,24 Radiological studies showed higher thigh muscle fat fraction and lower lean body mass. ALS4 patients have fatty infiltration in the muscles of their lower extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum creatinine levels have been reported to change significantly during the progression of other motor neuron diseases. 23,24 Radiological studies showed higher thigh muscle fat fraction and lower lean body mass. ALS4 patients have fatty infiltration in the muscles of their lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Among our ALS4 cohort, the male patients had significantly lower creatinine levels, which reflects a greater disease burden in males. Serum creatinine levels have been reported to change significantly during the progression of other motor neuron diseases . Radiological studies showed higher thigh muscle fat fraction and lower lean body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism was described as deeply involved in ALS pathophysiology [52,53]. In particular, several studies reported hyperlipidemia in patients with ALS [53][54][55][56][57], with a potential link with patient survival [53]. Close connections between IL-6 signaling and lipid metabolism exist [58,59].…”
Section: Moderate Effect On Metabolismmentioning
confidence: 99%
“…Creatinine concentrations are associated with disease severity as they are inversely correlated with ALSFRS-R scores and forced vital capacity [105][106][107]. The interpretation of this parameter remains very difficult as it depends on the muscle mass and on kidney function.…”
Section: Metabolites As Surrogate Endpointsmentioning
confidence: 99%